Plasticity after perceptual narrowing for voice perception: reinstating the ability to discriminate monkeys by their voices at 12 months of age - Friendly, Rayna H.; Rendall, Drew; Trainor, Laurel J. (Frontiers in Psychology, 2013)
Differentiating individuals by their voice is an important social skill for infants to acquire. In a previous study, we demonstrated that the ability to discriminate individuals by voice follows a pattern of perceptual narrowing (Friendly, et al., in press). Specifically, we found that the ability to discriminate between two foreign-species (rhesus monkey) voices decreased significantly between 6 and 12 months of age. Also during this period, there was a trend for the ability to discriminate human voices to increase. Here we investigate the extent to which plasticity remains at 12 months, after perceptual narrowing has occurred. We found that 12-month-olds who received two weeks of monkey-voice training were significantly better at discriminating between rhesus monkey voices than untrained 12-month-olds. Furthermore, discrimination was reinstated to a level slightly better that of untrained 6-month-olds, suggesting that voice-processing abilities remain considerably plastic at the end of the first year.